Influence of Control Strategy on Heat Recovery Efficiency in a Single-Duct Periodic Ventilation Device - Koper, Piotr (Energies (Basel), 2024)
The subject of the research was a single-duct, decentralised periodic ventilation unit, using accumulative heat exchanger for heat recovery (also called single-core fixed-bed regenerator). It can achieve high efficiency of heat recovery but is vulnerable to pressure differences between the interior of the building and the outside. To counter this, two control strategies were proposed: adjustment of the fan speed based on an air flow sensor and adjustment of the working cycle length based on temperature sensors. The strategies were tested experimentally in actual working conditions. Due to the use of cheap and simple sensors, it was possible to retain the low price of the device. Both control strategies proved to be successful in equalising the amount of supplied and removed air in a single cycle. Moreover, the heat recovery efficiency increased by more than 10% compared to the default working mode.